2016
DOI: 10.1002/anie.201602775
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole‐based Conjugated Polymers Bearing Branched Oligo(Ethylene Glycol) Side Chains for Photovoltaic Devices

Abstract: Conjugated polymers are essential for solution-processable organic opto-electronic devices. In contrast to the great efforts on developing new conjugated polymer backbones, research on developing side chains is rare. Herein, we report branched oligo(ethylene glycol) (OEG) as side chains of conjugated polymers. Compared with typical alkyl side chains, branched OEG side chains endowed the resulting conjugated polymers with a smaller π-π stacking distance, higher hole mobility, smaller optical band gap, higher di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 43 publications
3
113
0
Order By: Relevance
“…Our results are in agreement with previous reports that have shown that replacement of solubilizing chains can increase the dielectric constant . However, work done examining the effect of the increase of the dielectric constant via solubilizing chain modifications have shown that increase in performance only corresponds to changes in morphology, not the increased dielectric constant . The synthesis of TEG‐DPP‐BF is reported in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with previous reports that have shown that replacement of solubilizing chains can increase the dielectric constant . However, work done examining the effect of the increase of the dielectric constant via solubilizing chain modifications have shown that increase in performance only corresponds to changes in morphology, not the increased dielectric constant . The synthesis of TEG‐DPP‐BF is reported in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…While Donaghey et al reported nonfullerene acceptors with remarkably high dielectric constants up to 9.8 by adding oligo(ethylene oxide) chains to the backbones, no device performance was reported . In addition, oligo(ethylene oxide) chains have been attached to donor polymers, leading to an increase of dielectric constant from 2 or 3 for the polymers with alkyl side chains to ≈5 . Lu and Yang separately investigated polymers with fluorine atoms attached to polymer backbones and observed an increase in dielectric constant with fluorine substituents and an improvement in device PCE .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Fullerene derivatives were regarded as a promising electronic transport layer (ETL) material due to their distinguished advantages of high electron mobility and good energy level matching with the active layers of OSCs. [27][28][29][30][31] The polarities of the fullerene derivatives were influenced significantly by the presence of functional groups, such as sulfonate, ether chain, ester, and carboxylic acid [32][33][34][35] A few fullerene derivatives with functionalized anchoring groups have been developed as a modification layer of metal oxide in inverted OSCs. [36][37][38] They can be easily processed through a solution-based method, which demonstrated good compatibility between organic active layer and metal oxide.…”
Section: Doi: 101002/macp201800477mentioning
confidence: 99%